The effect of filter cakes enriched with soluble phosphorus used as a fertilizer on the sugarcane ratoons - Santos, Diego Henriques; Silva, Marcelo de Almeida [UNESP]; Tiritan, Carlos Sérgio; Crusciol, Carlos Alexandre Costa [UNESP] (Editora da Universidade Estadual de Maringá - EDUEM, 2014)
The objective of this work was to evaluate the effect of fertilization with filter cakes enriched with soluble phosphate on sugarcane ratoons. The experiment was performed from November 2007 to December 2009 at Presidente Prudente, São Paulo State, Brazil, in a completely randomized block design in a 4 x 4 factorial arrangement, with the first factor consisting of doses of filter cake (0, 1, 2 and 4 Mg ha-1) and the second doses consisting of phosphorus fertilizer (0, 50, 100, 200 kg ha-1 of P2O5) with 4 replicates. The following variables were evaluated: the number of tillers per meter, the leaf area index, soluble solids (ºBrix), stalk and sugar yield in the second crop cycle. We found a residual effect in the sugarcane ratoon after applying filter cakes enriched with soluble phosphate in the planting furrow. The initial tillering, leaf area index, stalk and sugar yield in the cane ratoon benefit from the application of filter cakes and soluble phosphate in the planting furrow. The best combination is filter cakes at a dose between 1.0 and 2.0 mg ha-1 with 100 to 200 kg ha-1 soluble phosphate applied at planting. This method obtains higher stalk and sugar yields for sugarcane ratoons.

O objetivo deste trabalho foi avaliar a cana-de-açúcar no ciclo de cana soca em função da adubação de plantio com torta de filtro enriquecida com fosfato solúvel. O experimento foi realizado entre novembro de 2007 e dezembro de 2009, em Presidente Prudente, Estado de São Paulo, em blocos ao acaso, no esquema fatorial 4 x 4, sendo o primeiro fator doses de torta de filtro (0; 1,0; 2,0 e 4,0 t ha-1) e o segundo doses de fósforo (0, 50, 100, 200 kg ha-1 de P2O5), com 4 repetições. As variáveis avaliadas foram números de perfilhos por metro, índice de área foliar, sólidos solúveis (ºBrix), produtividade de colmos e de açúcar no segundo corte. Houve efeito residual no ciclo seguinte da cana-de-açúcar com aplicação de torta de filtro enriquecida com fosfato solúvel no sulco de plantio. O perfilhamento inicial, o índice de área foliar, a produtividade de colmos e a de açúcar da cana soca foram beneficiados pela aplicação de torta de filtro e de fosfato solúvel no sulco de plantio. A melhor associação foi torta de filtro na dose 1,0 e 2,0 t ha-1 com fosfato solúvel entre 100 e 200 kg ha-1 no sulco de plantio em relação à produtividade de colmos e de açúcar na cana soca.
Efeito da torta de filtro associada à fósforo solúvel na soqueira da cana-de-açúcar
Keywords: Saccharum spp; Adubação organomineral; Superfosfato triplo; Cana-soca; Saccharum spp; Organo-mineral fertilizers; Triple superphosphate; Sugarcane ratoon